PKR downregulation prevents copper-induced synaptic dysfunction and cognitive impairment in a murine model of Wilson’s disease - Xu, Chenchen; Liu, Songyang; Cheng, Nan; Han, Yongsheng; Wang, Xinheng (Frontiers in Neuroscience, 2024)
Synaptic efficacy is critical for memory formation and consolidation. Accumulating evidence suggest that synapses are impaired during Wilson’s disease (WD), contributing to neuronal dysfunction and cognitive decline. WD is a prototypical condition among the copper metabolism disorders. Cognitive impairment is a common feature of affected patients with neurological symptoms, presenting as memory deficits, decreased cognitive flexibility, and impaired learning capabilities. These cognitive deficits can significantly impact the quality of life, affecting work and academic performance. However, the mechanisms mediating the inhibitory synaptic dysfunction in WD are incompletely understood. We investigated the effects of the double-stranded RNA-dependent protein kinase/eukaryotic initiation factor 2α (PKR/eIF2α) pathway on synaptic structure and function in WD using a murine model, toxic milk (TX mice). During mouse open-field tests, we noted a substantial rise in the mobility/immobility ratio among WD model animals compared to that in WT mice. Additionally, WD mice exhibited diminished central area exploration, as evidenced by reduced travel distance. Moreover, they displayed prolonged escape latency in the Barnes maze, suggesting that chronic copper accumulation is associated with neuropsychiatric alterations and cognitive impairment. We also found a decrease in the expression of synapse-associated proteins (synapsin 1, synaptophysin, postsynaptic density protein-93 [PSD93], postsynaptic density protein-95 [PSD95]), and vesicle-associated membrane protein2 [VAMP2]) besides abnormal neurotransmitter levels (including glutamate and GABA), indicating the presence of synaptic dysfunction in TX mice. Inhibiting PKR via C16 prevented these changes, suggesting that dysfunctional cognition is associated with the PKR/eIF2α pathway. We also observed changes in synapses, vesicles, dendritic spine density, and dendritic length that were associated with the presence of cognitive dysfunction. Further investigation revealed that C16 treatment decreased the TUNEL-positive cell numbers in the hippocampus of TX mice and prevented 8-OHdG-induced synaptic dysfunction. Results suggest that PKR downregulation prevents copper-induced synaptic dysfunction in the murine WD model. Therefore, targeting PKR pharmacologically may be a potential therapeutic strategy for treating the copper-induced neuropathology of patients with WD.